MANFAAT PEMBERIAN GELOMBANG ULTRASONIK INTENSITAS RENDAH UNTUK MEMPERCEPAT PEMBENTUKAN KALUS FRAKTUR TIBIA - Hantoko, Sidho; Dradjat, Respati Suryanto (Jurnal Kedokteran Brawijaya, 2003)
ABSTRACT Fracture healing relative require more times.  Many effort have been done to shorten the time, including stimulation with low intensity ultrasonic.    Invitro  studies  and  animal  experimentation  have  been  proved  in  various  results.  Physical  therapy  equipments  in  the hospitals using ultrasonic wave posible to stimulate process of fracture healing. Clinical experimental study was done in our series, the samples was divided randomly into 2 groups.  One group was stimulated with low intensity ultrasonic from Sonopuls-591 with 1 MHz frequency, 0,2 W/cm2 intensity, for 15 minutes.  The other group withuot stimulation as the control group.  The variable were pain, sticky, and callus formation were evaluated perodically. The Results were the degrees of pain in control group higher than control. The bony union (sticky) was no difference within both group.  The callus formation was higher in the treatment group (p = 0,069). Our Conclusion is 15 minutes Low intensity ultrasonic stimulation, that was given 10 times within 3 days time interval was significanly  increase callus formation (p = 0,069). Key words: Fracture healing, ultrasonic, callus formation.